PENERAPAN MEDIA SMART BOX UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI KONSEP TATA SURYA DI SD NEGERI BRUMBUNGAN LOR - Rizka Amelia Putri; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low student learning outcomes are caused by students who are less active and have no interest in learning, as evidenced by the fact that some students are still busy playing with their friends, going around the class and the lack of use of learning media used by the teacher during KBM. Good concept understanding is essential for students. This is because the essence of learning material is to understand the meaning behind each process. Therefore, there needs to be a solution to activate students and improve student learning outcomes with the help of learning media. So the researcher took the initiative to apply smart box media in IPAS subjects which aims to determine the improvement of learning outcomes of grade VI students on the concept of the solar system. The research method implemented is Classroom Action Research by conducting 2 cycles including 4 meetings and each cycle has four steps: (planning, implementation, observation, and reflection). Data collected includes interview, observation, test and documentation techniques. The subjects of this study were 15 students. This study shows that there is an increase in student learning outcomes from before and after the class research action from Cycle I to Cycle II by applying smart box media. Pre-cycle data from a total of 15 students, there were 7 students who showed learning completeness showing the average student score was 58.6 and the percentage of completeness was only 46.6%. The first cycle produced an average score of 68 and the percentage of completeness was 66.6%. Whereas in the second cycle the number of students who successfully achieved learning completeness was 14 students and only 1 student remained who was still not complete. The average student score obtained increased to 84.6 and the percentage of completeness to 93%.